Space-harmonic effects in helical slow-wave structure - An equivalent circuit analysis - Ghosh S.; Sinha A.K.; Gupta R.K.; Joshi S.N.; Jain P.K.; Basu B.N. (My University, 2025)
The analysis of a lossless helical slow-wave structure (SWS) using equivalent circuit approach, reported elsewhere, had been carried out for the fundamental mode only. This is essentially used to predict the transmission line parameters. Moreover, in the analysis the effect of permittivity on the radial propagation constant has not been considered. The radial propagation constant was considered to be same over the different structure regions. In this paper, the analysis has been developed for the space-harmonic modes considering different radial propagation constant over different structure regions. Due to it, the present analysis becomes more general, accurate and capable of dealing with a wide range of structure parameters. The dispersion relation developed here in terms of the equivalent line parameters for a lossless structure, namely, shunt capacitance per unit length and series inductance per unit length for the space-harmonic modes, as a special case, passes on to those obtained earlier by considering same radial propagation constants over different structure regions and for the fundamental mode. Besides the dispersion characteristics, characteristics impedance has also been predicted in terms of line parameters. The results presented here in terms of the structure parameters can be used for structure design and performance evaluation as well as for the control of any space harmonic of interest. The present analysis has also been validated with those experimental values reported elsewhere.